(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: The scope of the present study was to evaluate the results obtained from implementing the integrated programme of sustainable entrepreneurship specific to balneal tourism in the pre- and post-pandemic period at the Balneal and Rehabilitation Sanatorium of Techirghiol (SBRT), with the identification of current trends and preferences of the population regarding healthcare services in the Techirghiol area. Methods: The retrospective longitudinal study, conducted from 2018 to 2022, used data gathered in SBRT services on a number of patients grouped by condition, the quality of therapeutic water accessed by patients and of waste water discharged into the lake, books and documents specific to the proposed topic. Results: Starting with the pandemic year 2020, patients are also referred to SBRT for treatment of post covid after-effects (restrictive/obstructive respiratory diseases). Water waste discharged into Lake Techirghiol in 2020 exceeds the legal limits for the arithmetic mean values of nitrogen ammonia, returning to normal in 2021 (2.88 mg/l), reaching 0.24mg/l in 2022. Considering the 2020 pandemic year as the reference year, the number of tourists in 2020 decreased by 58% compared to 2018 and by 37% compared to 2019, with an increase of 42% and 43% in 2021 and 2022 respectively. Conclusions: The number of patients accessing natural factor therapies in the time period analysed has seen a steady post-pandemic increase. The sustainable development of spa tourism in the Techirghiol area requires an integrative approach that ensures environmental protection. .